A favourable ecosystem for scientific translation projects: Strasbourg’s role in the production and transnational circulation of knowledge in the 1780s - Fischer, Daniel (chronotopos – A Journal of Translation History, 2024)
Strasbourg’s geographical and political position during the eighteenth century led to the longstanding assumption that the capital of Alsace naturally fostered the circulation of German and French ideas and knowledge. Throughout the century, many travellers flowed through this city on the Rhine, which was viewed as the Eastern gateway to France even though its population remained primarily German-speaking. This study reconstitutes Strasbourg’s total catalogue of 189 publications during the 1780s, enabling us to assess the provincial city’s role in producing and circulating knowledge on both sides of the Rhine and more widely in Europe leading up to the French Revolution. We examine evidence of the reasons for the large volume of scientific publications, including a surprising level of investment into German translations. Finally, we present the specific case of the translated works of Lavoisier and Ehrmann published in Strasbourg in 1787, revealing new details that indicate that the local publishing sector’s rationale went beyond geographical and linguistic opportunities.